Pronomina Persona Omae pada Komik One Piece Volume 17 Karya Eichiro Oda - Sharnetta Florenzia Godjali (Universitas Dian Nuswantoro, 2019)
Â This research disccusses about the use of personal pronoun omae on comic One Piece Volume 17. The purpose of this research is to analyse how using second person pronoun omae. In the concept uchi-soto which applied by the speakers for the interlocutors. The data of this research were analyzed by using uchi-soto concept proposed by Nakane Chie and Hirabayashi-Hama. It also discusses the factors of using polite language. The result of the data analysis show that omae is used in formal and informal context. It also used by the speakers to speak with various kind of interlocutors : close friends, outsiders, or enemies. It also used by both female and male.Â Keyword : Second Person Pronouns, uchi-soto, omae, speaker, listener